All the sinners bleed : a novel [compact disc, unabridged] - Cosby, S. A. (Macmillan Audio, 2023)
Titus Crowne is the first Black sheriff in the history of Charon County. A former FBI agent and security expert, Titus came home to take care of his father and look out for his troubled younger brother. He ran for Sheriff to make a difference, especially in the Black community which has so often been treated unfairly by the police. But a year to the day after his election, a school shooting rocks the town. A beloved teacher is killed by a former student, and as Titus attempts to deescalate and get the boy to surrender, his deputies fire a fatal shot. In the investigation, it becomes clear that the student they shot had been abused by the dead teacher, as well as by unidentified perpetrators. The trail leads to buried bodies, and secrets. While Titus tries to track down a killer hiding in plain sight, while balancing daily duties like protecting Confederate pride marchers, he must face what it means to be a Black man wearing a police uniform in the American South.